A Kinetic Monte Carlo Approach for Self-Diffusion of Pt Atom Clusters on a Pt(111) Surface (Communications in Computational Physics, 2011)
A lattice Kinetic Monte Carlo (KMC) approach is considered to study thestatistical properties of the diffusion of Pt atom clusters on a Pt(111) surface. The interatomicpotential experienced by the diffusing atoms is calculated by the embeddedatom method and the hopping barrier for the allowed atomic movements are calculatedusing the Nudged Elastic Band method. The diffusion coefficient is computedfor various cluster sizes and system temperatures. The obtained results are in agreementwith the ones obtained in previous experimental and theoretical works. A simplescaling argument is proposed for the size dependence of the diffusion coefficient's prefactor.A detailed statistical analysis of the event by event KMC dynamics reveals twoimportant and co-existing mechanisms for the diffusion of the cluster's center of mass.At low temperatures (below T=400K) the dominating mechanism responsible for thedisplacement of the cluster's center of mass is the periphery (or edge) diffusion of theatoms. At high temperatures (above T=800K) the dissociation and recombination ofthe clusters becomes more and more important.